The Development of Problem-Based Student Worksheets To Improve Mathematical Reasoning Ability In Class XI Students Of SMA Negeri 6 Surakarta - Rofi'ah, Intan (Universitas Muhammadiyah Surakarta, 2021)
This research aims to develop a valid, practical, and effective problem-based Student Worksheet (LKPD) to improve students' mathematical reasoning ability in class XI IPS 1 SMA Negeri 6 Surakarta. The development research method used is a 4-D model, including Define, Design, Develop, and Dissemination. The subjects in this study were students of class XI IPS 1 SMA Negeri 6 Surakarta. Data collection techniques used interviews, questionnaires, observations, and tests of mathematical reasoning abilities. This research analyses the validity, practicality, and effectiveness of LKPD using criteria scores and test results of mathematical reasoning abilities through a t-test with a significance level of 5%. Based on the analysis results, the developed LKPD meets the criteria of being valid, practical, and effective. Problem-based LKPD declared valid with 79% between the average results of expert assessments and readability tests; practical rated 86% in the intermediate results of observations of the implementation of learning and student responses; effective because there is an increment in students' mathematical reasoning abilities after using LKPD with an adequate level of 0.47 including in the medium category.